2019
DOI: 10.3390/ijms20184516
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wharton Jelly-Derived Mesenchymal Stromal Cells and Their Conditioned Media in the Treatment of a Rat Spinal Cord Injury

Abstract: The transplantation of Wharton’s jelly derived mesenchymal stromal cells (WJ-MSCs) possesses therapeutic potential for the treatment of a spinal cord injury (SCI). Generally, the main effect of MSCs is mediated by their paracrine potential. Therefore, application of WJ-MSC derived conditioned media (CM) is an acknowledged approach for how to bypass the limited survival of transplanted cells. In this study, we compared the effect of human WJ-MSCs and their CM in the treatment of SCI in rats. WJ-MSCs and their C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 49 publications
(66 reference statements)
3
41
1
Order By: Relevance
“…Given the fact that similar neurological injuries may occur in most cases of SCI, we have developed a standard contusion injury model of rat, in which the spinal cord is vertically contused from a de ned height and with a xed force correlating with severe neurological injury and weak functional recovery. In previous studies, cell transplantation for SCI was performed by direct injection into the injured spinal cord parenchyma [41][42][43]. However, direct injection into the spine lesion with a needle would be clinically unrealistic, and the procedure itself is potentially harmful to the parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that similar neurological injuries may occur in most cases of SCI, we have developed a standard contusion injury model of rat, in which the spinal cord is vertically contused from a de ned height and with a xed force correlating with severe neurological injury and weak functional recovery. In previous studies, cell transplantation for SCI was performed by direct injection into the injured spinal cord parenchyma [41][42][43]. However, direct injection into the spine lesion with a needle would be clinically unrealistic, and the procedure itself is potentially harmful to the parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Because WJ-MSCs exert neuroprotective and neurotrophic effects, attempts have been made to also utilize them in spinal cord injury treatment. After the intrathecal transplantation of WJ-MSCs into rats with spinal cord injury, in several studies, the observed effects were similar, namely, an improved locomotor recovery and higher amount of spared gray matter compared to the controls [10,83,84]. Krupa et al [83] tested two dosages of cells (0.5 M and 1.5 M), which were administered one to three times in weekly intervals.…”
Section: Selected Animal Modelsmentioning
confidence: 99%
“…The results indicated that the effects of treatment are dose-dependent, as 1.5 M of cells provided a better outcome than 0.5 M, and this was enhanced by repeated application [83]. Chudickova et al [84] compared the results of therapy with WJ-MSCs or their culture media (CM), as beneficial effects of MSCs are exerted mainly in a paracrine manner. Compared to the treatment with stem cells, the use of culture medium improved axonal sprouting and reduced the number of reactive astrocytes; therefore, the use of CM instead of the cells themselves seems to be an attractive alternative for spinal injury treatment [84].…”
Section: Selected Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most studies showed evidence that MSCs most likely act through their secretions (paracrine effect) [46][47][48] and not via their own integration/differentiation within the host tissue, some authors have reported the potential for MSCs transdifferentiation in cells of the nervous system and have shown that, after infusion into the spinal cord, these cells possibly promote regeneration of neurons because they have neuronal markers [49][50][51][52] . In vitro studies have shown that BM-MSC possess an intrinsic capacity to differentiate into neural-like and glial-like cells and express nestin, βIII-tubulin, neurofilaments, neuronspecific enolase, and glial fibrillary acidic protein (GFAP) [53][54][55] .…”
Section: Stromal Cells Therapymentioning
confidence: 99%